Development and preliminary assessment of a CRISPR–Cas12a-based multiplex detection of Mycobacterium tuberculosis complex - Xiao, Jing; Li, Jieqiong; Quan, Shuting; Wang, Yacui; Jiang, Guanglu; Wang, Yi; Huang, Hairong; Jiao, Weiwei; Shen, Adong (Frontiers in Bioengineering and Biotechnology, 2023)
Since the onset of the COVID-19 pandemic in 2020, global efforts towards tuberculosis (TB) control have encountered unprecedented challenges. There is an urgent demand for efficient and cost-effective diagnostic technologies for TB. Recent advancements in CRISPR–Cas technologies have improved our capacity to detect pathogens. The present study established a CRISPR–Cas12a-based multiplex detection (designated as MCMD) that simultaneously targets two conserved insertion sequences (IS6110 and IS1081) to detect Mycobacterium tuberculosis complex (MTBC). The MCMD integrated a graphene oxide-assisted multiplex recombinase polymerase amplification (RPA) assay with a Cas12a-based trans-cleavage assay identified with fluorescent or lateral flow biosensor (LFB). The process can be performed at a constant temperature of around 37°C and completed within 1 h. The limit of detection (LoD) was 4 copies μL−1, and no cross-reaction was observed with non-MTBC bacteria strains. This MCMD showed 74.8% sensitivity and 100% specificity in clinical samples from 107 patients with pulmonary TB and 40 non-TB patients compared to Xpert MTB/RIF assay (63.6%, 100%). In this study, we have developed a straightforward, rapid, highly sensitive, specific, and cost-effective assay for the multiplex detection of MTBC. Our assay showed superior diagnostic performance when compared to the widely used Xpert assay. The novel approach employed in this study makes a substantial contribution to the detection of strains with low or no copies of IS6110 and facilitates point-of-care (POC) testing for MTBC in resource-limited countries.